Effect of salting method on salt concentration in Dhaka cheese (Progressive Agriculture, 2015)
This research was conducted to study the effect of salting method on salt concentration in Dhaka cheese. Dhaka cheese was made in the laboratory on pilot scale and salted either by dry salting, or salt stuffing, or brining, or their combinations. Two levels of dry salting was applied, 1% and 2%, w/w. The use of different salting method had a significant (P